2016
DOI: 10.1016/j.jvolgeores.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling textural heterogeneity in obsidian: Shear-induced outgassing in the Rocche Rosse flow

Abstract: Obsidian flow emplacement is a complex and understudied aspect of silicic volcanism. Of particular importance is the question of how highly viscous magma can lose sufficient gas in order to erupt effusively as a lava flow. Using an array of methods we study the extreme textural heterogeneity of the Rocche Rosse obsidian flow in Lipari, a 2 km long, 100 m thick,~800 year old lava flow, with respect to outgassing and emplacement mechanisms. 2D and 3D vesicle analyses and density measurements are used to classify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 103 publications
(183 reference statements)
1
28
0
Order By: Relevance
“…Rhyolitic lava flows show a complex internal sequence with variably vesicular, devitrified and deformed textures, and complex surface deformation patterns (Fink 1978(Fink , 1983Manley and Fink 1987;Shields et al 2016). The traditional view of rhyolitic flow interiors includes (from the surface downwards) an upper breccia, thick obsidian, foliated rhyolite, thinner obsidian and a basal breccia (Fink 1978(Fink , 1983Manley and Fink 1987).…”
Section: Lithofacies Of Rhyolitic Lava Flowsmentioning
confidence: 99%
See 4 more Smart Citations
“…Rhyolitic lava flows show a complex internal sequence with variably vesicular, devitrified and deformed textures, and complex surface deformation patterns (Fink 1978(Fink , 1983Manley and Fink 1987;Shields et al 2016). The traditional view of rhyolitic flow interiors includes (from the surface downwards) an upper breccia, thick obsidian, foliated rhyolite, thinner obsidian and a basal breccia (Fink 1978(Fink , 1983Manley and Fink 1987).…”
Section: Lithofacies Of Rhyolitic Lava Flowsmentioning
confidence: 99%
“…Shields et al (2016) identified four textural units in the Rocche Rosse: type 1-glassy obsidian, which is spherulitic and has a low vesicularity (< 15%); type 2-'frothy' obsidian, which is vesicular (30-60%) and glassy, with large elongated vesicles perpendicular to banding; type 3-pumiceous lava, which is highly vesicular (40-60%), with variable vesicle sizes; type 4-shear banded lava, characterised by a low-medium vesicularity (20-40%), and highly deformed and coalesced vesicles. Glassy obsidian and shear banded lavas occur as massive and/or platy outcrops, pumiceous lava is observed throughout the flow and 'frothy' obsidian makes up fold hinges, tension gashes, micro folding and extensional fractures (Shields et al 2016).…”
Section: Lithofacies Of Rhyolitic Lava Flowsmentioning
confidence: 99%
See 3 more Smart Citations